THE EUROPEAN COURT ON HUMAN RIGHTS: THE PROBLEM OF UNENFORCEABLE JUDGMENTS - Stanislav V. Chernichenko (Московский журнал международного права, 2018)
INTRODUCTION. The paper demonstrates that the problem of implementing judgments of the European Court of Human Rights does exist if such a judgment is not in line with the Constitution of the Russian Federation. This problem is caused in legal dimension by the two different factors. On the one hand the Constitution of the Russian Federation “shall be the supreme law and shall be in force throughout the territory of the Russian Federation. No laws or other legislative acts … shall contravene the Constitution of the Russian Federation” (Article 15 Part 1). On the other hand, a State may not invoke its internal (national) law as justification for its failure to perform a treaty (Article 27 of the Vienna Convention on the Law of Treaties, 1969).MATERIALS AND METHODS. Research materials include judgments of the European Court of Human Rights and Orders of the Constitutional Court of the Russian Federation and also the teachings of the most qualified scholars in International Law which are relevant to the title of this paper. General and specific scientific methods are used by the author. In the context of applicable general international law the paper considers both judgments o the European Court of Human Rights and orders of the Constitutional Court of the Russian Federation paying specific attention to the reasons of different legal positions adopted by these Courts.RESEARCH RESULTS. The widening of the competence of the Сonstitutional Court of Russia in December 2014 arouses apprehension. The Court pointed out that two judgments of the European Court on Human Rights were unenforceable: (1) on the judgment on the application of Anchugov and Gladkov and (2) on the judgment concerning the application of UKOS. In the first case the European Court on Human Rights admitted that Russia was responsible for moral damage and the recognition of it was enough for compensation. In the second case the European Court on Human Rights admitted that Russia violated Protocol No.1 to the Convention on Human Rights. In connection with it Russia must compensate the pecuniary damage. It is confirmed by the Committee of Ministers (the Council of Europe).DISCUSSION AND CONCLUSIONS. The Constitutional Court of the Russian Federation indeed has (as its professional function) an obligation to legally protect the national interests of Russia if they are questioned by a judgment of a foreign court which does not correspond to International Law. But in cases considered in this paper the Constitutional Court of Russia while addressing the judgments of the European Court of Human Rights (which are in contradiction with the International Law) made itself a legal mistake from the point of International Law. According to Article 26 of the Vienna Convention on the Law of Treaties, 1969, every treaty in force is binding upon the parties to it and must be performed by them in good faith”. Even in the case when the national law provides for a different approach (article 27 of the same Convention). The Constitution of any State is a part of its national law. So the 1969 Convention’s rules of Articles 26 and 27 are applicable also to Constitutions. While stating that the Constitution has a higher legal value then International Treaty of the Russian Federation, the Constitutional Court thus undermines the national interests of Russia in maintaining legal order and the Rule of Law in international relations.